2022
DOI: 10.3389/fpsyt.2021.827541
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbances and Depression Are Co-morbid Conditions: Insights From Animal Models, Especially Non-human Primate Model

Abstract: The incidence rates of depression are increasing year by year. As one of the main clinical manifestations of depression, sleep disorder is often the first complication. This complication may increase the severity of depression and lead to poor prognosis in patients. In the past decades, there have been many methods used to evaluate sleep disorders, such as polysomnography and electroencephalogram, actigraphy, and videography. A large number of rodents and non-human primate models have reproduced the symptoms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 135 publications
0
2
0
Order By: Relevance
“…Sleep disorders were not only a common symptom of depression but could also be its rst presenting sign [52]. Prolonged lack of good sleep could cause physical and psychological fatigue, making individuals more susceptible to depressive moods [53]. Studies had revealed a statistically signi cant bidirectional correlation between insomnia and hypertension [54].…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disorders were not only a common symptom of depression but could also be its rst presenting sign [52]. Prolonged lack of good sleep could cause physical and psychological fatigue, making individuals more susceptible to depressive moods [53]. Studies had revealed a statistically signi cant bidirectional correlation between insomnia and hypertension [54].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, poor sleep may affect the emotional regulation ability of the individual through a physiological mechanism[ 68 ], and a lack of sleep increases the threat across multiple domains of dysfunction[ 69 ]. Sleep is associated with depression at the molecular and neurophysiological levels, and abnormalities in these neurotransmitter systems associated with sleep disorders may contribute to the exacerbation of depression[ 70 ]. In addition, sleep disorders affect students’ daytime function, resulting in daytime sleepiness, drowsiness, and inattention.…”
Section: Discussionmentioning
confidence: 99%
“…The visualizations completed for the top four continuous covariates were concordant with current literature: there is strong epidemiological evidence that sleep problems are heavily linked with depression. Multiple papers have found difficulty falling asleep and decreased hours of sleep with increased depression [41][42][43][44][45][46][47][48][49][50][51][52][53]. Additionally, depression has bene linked to lower quality sleep and increased day time exhaustion [31,34,46,54,55].…”
Section: Plos Onementioning
confidence: 99%